2011
DOI: 10.1136/ard.2010.135665
|View full text |Cite
|
Sign up to set email alerts
|

A novel Saa3-promoter reporter distinguishes inflammatory subtypes in experimental arthritis and human synovial fibroblasts

Abstract: The Saa3-promoter reporter demonstrates a robust and feasible tool for assessing the course and severity of experimental arthritis and for distinguishing molecularly distinct inflammatory SF subtypes from a heterogeneous patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Multiple factors with potential proinflammatory and cartilage-degrading activities may be differentially expressed by RASFs and OASFs 7 10 22. However, the similarities and differences between RASFs and OASFs cannot be interpreted without including additional controls from normal synovial tissues 12 17 23. In this study, we investigated the transcriptomic profile of OASFs as compared to those of RASFs and HSFs.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors with potential proinflammatory and cartilage-degrading activities may be differentially expressed by RASFs and OASFs 7 10 22. However, the similarities and differences between RASFs and OASFs cannot be interpreted without including additional controls from normal synovial tissues 12 17 23. In this study, we investigated the transcriptomic profile of OASFs as compared to those of RASFs and HSFs.…”
Section: Introductionmentioning
confidence: 99%
“…screened synovial genes whose expression is significantly up-regulated during the course of rheumatoid arthritis23. The Saa3 promoter (−314/+50) showed strong transcriptional induction in synovial fibroblasts in rheumatoid arthritis, suggesting that this promoter region is involved in the response to the inflammatory process in this disease2324. Here, to examine whether the Saa3 promoter activity can respond to activated macrophages, we constructed an Saa3 promoter-luciferase chimeric gene (Saa3-luc) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three CCAAT/enhancer-binding protein β (C/EBPβ)-binding sites are present in the mouse Saa3 region (−152, −107, and −77)2427. Because previous studies showed that C/EBPβ responds to inflammatory stimuli including IL-1 and TNF-α, we tested the role of C/EBPβ in the responsiveness of the Saa3 promoter to activated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Several promoters showed an inducible profile in lentivirally transduced macrophage and fibroblast cell lines after in vitro stimulation with lipopolysaccharide. In addition, the Saa3 promoter was able to detect differences between high and low inflammatory profiles in synovial fibroblasts from patients with rheumatoid arthritis (RA) and osteoarthritis 4. This proved the inducibility and sensitivity of this promoter to disease activity.…”
Section: Introductionmentioning
confidence: 84%